INSIGHTS INTO BEYOND-LIFE COMPLEX SYSTEMS SUFFERING FROM OBSOLESCENCE - Lambert, Keith Richard (The South African Journal of Industrial Engineering, 2018)
Supporting and maintaining complex systems in developing countries has numerous challenges, especially in systems that suffer from obsolescence and operate beyond their designed life. Existing methodologies in developing an integrated logistics support system (ILSS) in developed countries are based on resources that are readily available, while in developing countries this is not always the case, and so grounded design rules within a robust framework are required. Various methods and six case studies of high technology systems were used for this paper. Obsolescence effects are considerably wider than the retirement and obsolescence component of present frameworks.